NUTELLA VERSUS NUTELLA, REPUBLIC OF MACEDONIA VERSUS FYROM (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Starting from the fact that double standards exist in the policies andlegislative acts in the European Union, as regards to food products andfood distribution in the EU market, like for example in Germany andAustria food products are being placed on the market with a higherquality and more accessible prices, while in Bulgaria and SlovakRepublic the same products that are being distributed are of lowerquality and higher prices. The situation is similar in the field of EU’sForeign Policy towards acceeding countries. For example the EU hasgranted membership to Cyprus and Croatia that still have openterritorial disputes, but on the other side the EU has stalled the Eurointegrativeprocesses for Republic of Macedonia because of its namedispute, where in spite of international documents that guarantee theright of Republic of Macedonia for membership in internationalorganizations, the EU does not take them in consideration. In base ofthat, the purpose of the paper is to investigate the coherence of theForeign policy of the European Union towards Republic of Macedoniavis-á-vis the membership of Cyprus and Croatia.